2017
DOI: 10.1089/thy.2016.0186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adequate Iodine Supply on the Incidence of Iodine-Induced Thyroid Disorders in Slovenia

Abstract: After the increase in iodine supply, a higher incidence of II-Hypo and a lower incidence of II-Hyper were observed than before the increase. Less severe II-Hyper, shorter duration of treatment of II-Hyper, as well as a longer thyroid disease-free period in patients on amiodarone are additional beneficial clinical consequences after the establishment of an adequate iodine supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Even small increases in iodine intake are associated with a small increase in the prevalence of subclinical hypothyroidism, particularly if the iodine intake increases from deficient to more than adequate within a short time. In a hospital‐based retrospective study of 885 Slovenian adults, an increase in the incidence of iodine‐induced hypothyroidism was observed from 5% in 2 years before to 20% in 10 years following a mandatory increase in salt iodization levels from 10 to 25 mg/kg in 1999 …”
Section: Thyroid Disorders Associated With Iodine Excessmentioning
confidence: 99%
See 1 more Smart Citation
“…Even small increases in iodine intake are associated with a small increase in the prevalence of subclinical hypothyroidism, particularly if the iodine intake increases from deficient to more than adequate within a short time. In a hospital‐based retrospective study of 885 Slovenian adults, an increase in the incidence of iodine‐induced hypothyroidism was observed from 5% in 2 years before to 20% in 10 years following a mandatory increase in salt iodization levels from 10 to 25 mg/kg in 1999 …”
Section: Thyroid Disorders Associated With Iodine Excessmentioning
confidence: 99%
“…In a hospital-based retrospective study of 885 Slovenian adults, an increase in the incidence of iodine-induced hypothyroidism was observed from 5% in 2 years before to 20% in 10 years following a mandatory increase in salt iodization levels from 10 to 25 mg/kg in 1999. 139 The development of hypothyroidism following chronic excess iodine exposure may be due to increased thyroid autoimmunity, the presence of elevated antithyroid antibodies. 57,130,140 Thyroid autoimmunity Excessive iodine consumption has been widely described as a risk factor for the development of thyroid autoimmunity.…”
Section: Hypothyroidismmentioning
confidence: 99%
“…In Slovenia, iodine increased from 10 to 25 mg of potassium iodide per kg of salt in 1999. Thyroid epidemiology was observed over the successive years, up to 2014: although diffuse goiter and hyperthyroidism incidence decreased (the latter with a higher proportion of subclinical cases than in the past), no long-term changes were observed for GD, while the incidence of TMNG and solitary nodule transiently increased or remained unchanged ( 25 , 26 , 27 ). Study design, population’s characteristics (the most important being age), observation periods, and the combination between the entity of the iodine deficiency and the strategy of iodine prophylaxis campaign could all play a role in the heterogeneity of these results.…”
Section: Discussionmentioning
confidence: 99%
“…Koukkou et al concluded that excessive iodine intake might contribute to excessive thyroid hormone synthesis and release, inducing autonomic thyroid function and increasing the risk of iodine-induced hyperthyroidism in those living in abundant iodine areas [ 37 ]. Bajuk et al have reported that high iodine intake reduced the incidence of iodine-induced hyperthyroidism in Slovakians ( P < 0.001) [ 38 ]. Park et al have demonstrated that excessive iodine intake did not affect hyperthyroidism in a Korean cohort [ 39 ].…”
Section: Discussionmentioning
confidence: 99%